CAMBIOS EN LAS PROPIEDADES EDAFOLÓGICAS EN EL TIEMPO EN UN BOSQUE TEMPLADO DEL ESTADO DE HIDALGO, MÉXICO CHANGES IN SOIL PROPERTIES IN THE TIME IN A TEMPERATE FOREST OF STATE OF HIDALGO, MEXICO - Fuentes-Andrade, María del Socorro; Acevedo-Sandoval, Otilio Arturo; Cruz-Chávez, Enrique; Otazo-Sánchez, Elena María; Román-Gutiérrez, Alma Delia (European Scientific Journal, ESJ, 2014)
Changes in soil properties were evaluated in a temperate forest located in the town of San Mateo Acaxochitán, Hidalgo, Mexico. Soil samples were taken at four depths in two periods (2004, S-04 and 2011, S- 11) to the results we applied the principal component analysis, the component one explained 51 % of variance; presented positive correlation between the variables S-04K, S-11NT, S11CO, S-04NT and S-04CO (group a), S-11pHact, S-04Da , S-04Ca , and S-04Mg (group b) and negative correlation between the variables: S-11Da, S-11Alint, S-11Dr, S-11Acint, and S-11PT (group c), and S-11C/N and S-04C/N (group d). The component two explained 31 % of variance , presented positive correlation between the variables: S-11PT, S-11Acint, S-04Mg , and S- 04Ca (group c) and negative correlation between S-04C/N and S-11C/N (group d). The analysis of variance showed that the soil variables that showed significant differences ( ≤ 0.05 ) between the S-04 and S-11 were: PT, Dr, pHpot , Acint , NT , K+ and Ca2+ .